Las dos caras del patroncito de El Teatro Campesino y su adaptaci?n al Ecuador - Ruiz, José Salvador (Latin American Theatre Review, 2007)
This article studies Las dos caras del patroncito and its adaptation to Ecuador by the Ollantay theatre group. It argues that the humorous and socio-political elements of Las dos caras del patroncito make this chicano piece a "continental" play, one that transcends California and that can be adapted to other countries in Latin America. This article compares both adaptations of the social and political contexts in which they were created as well as the influence of Brecht in the plays. (JSR, in Spanish)